A Study on Simulation Methods for AGV Fleet Size Estimation in a Flexible Manufacturing System. (2018) - Valmiki, Puneeth; Simha Reddy, Abhinav; Panchakarla, Gowtham; Kumar, Kranthi; Purohit, Rajesh; Suhane, Amit
Abstract: This paper presents a study on the estimation of fleet size of Automated Guided Vehicle (AGV). Determination of AGV fleet size plays a decisive role on the performance of job shop environment. Simulation methods are studied in detail for the estimation of AGV fleet size in a Flexible Manufacturing System. The presented methods are based on either minimization of total travel time or overall cost. Analytical methods are used for initial estimation of fleet size. Simulation methods give better results but in complex situations, simulation methods are cumbersome.